Study on soluble heavy metals with preconcentration by using a new modified oligosilsesquioxane sorbent - Vieira, Eduardo G. [UNESP]; Soares, Isaac V. [UNESP]; Dias Filho, Newton L. [UNESP]; da Silva, Nileia C. [UNESP]; Perujo, Sergio D. [UNESP]; Bastos, Andrea C. [UNESP]; Garcia, Edemir F. [UNESP]; Ferreira, Tamires T. [UNESP]; Fraceto, Leonardo F. [UNESP]; Rosa, Andre H. [UNESP] (Elsevier B.V., 2012)
In this work, a new modified oligosilsesquioxane was prepared, characterized and evaluated for its heavy metal adsorption characteristics from aqueous solution. The material was characterized using infrared spectroscopy, X-ray diffractometry, solid-state Si-29 and C-13 nuclear magnetic resonance. Batch and column experiments were conducted to investigate for Fe (III), Cr (III), Cu (II), Cd (II), Pb (II) and Ni (II) removal from dilute aqueous solution by sorption onto modified oligosilsesquioxane. The results obtained in the flow experiments, showed a recovery of ca. 100% of the metal ions adsorbed in a column packed with 2.0 g of nanomaterial, using 3 mL of 1.0 mol L-1 HCl solution as eluent. The detection limits for Fe, Cr, Cu, Cd, Pb, and Ni were 0.26, 0.33, 0.38, 0.41, 0.47 and 0.55 mu g L-1, respectively. The relative standard deviation values (n = 12) were <4.82% for Fe, <4.12% for Cr, <3.79% for Cu, <3.03% for Cd, <4.02% for Pb and <2.65% for Ni. The proposed method was successfully applied to the analysis of environmental samples.
Keywords: Preconcentration; Adsorption; Isotherms; Oligosilsesquioxane; Heavy metals